Pengaruh kepuasan konsumen terhadap kesetiaan Merek (studi kasus Restoran Popeye Chicken Express dan Restoran Yogya Chicken di Yogyakarta) - Arif Fakhrudin, SE (MM 11 UMY 069, 2011)
This study aimed to test the eï¬‚ect of customer satisfaction on brand loyalty at Popeye 's Chicken Express & Yogya Chicken Restaurant. Independent variables in this stuafy are the attributes that include the formation of customer satisfaction; attributes related to the product, attributes related to the service, attributes related to the purchase. The dependent variable in this research is brand loyalty. The subject of this research is a restaurant customer Popeye Chicken Express & Yogya Chicken. The sampling technique using a purposive sampling of respondents who never make purchases in the Popeye 's Chicken Express and a minimum of two times the respondent had ever made a purchase in Yoga Chicken least two times. Data collection techniques using primary data that is create a questionnaire that lists filled out by customers Popeye 's Chicken Express & Yogya Chicken Restaurant. Analysis of data using multiple regression analysis, F test and t test, different test independent- sample T test. The results of this study are: (a) There are positive. and signiï¬cant inï¬‚uence between customer satisfaction which includes attributes related to the product, attributes related to the service, attributes related to the purchase together to brand loyalty. (b) There are positive and significant inï¬‚uence between customer satisfaction on attributes related to the product of brand loyalty. (0) There are positive and signiï¬cant inï¬‚uence between customer satisfaction on attributes related to the service of brand loyalty. (aD There are positive and significant inï¬‚uence between customer satisfaction'on attributes related to the purchase on brand loyalty. (e) There are diï¬erences in the level of customer satisfaction between P0peye's Chicken Express and Yoga Chicken Restaurant.